Cognitive subtypes of probable Alzheimer's disease robustly identified in four cohorts. Issue 11 (17th April 2017) - Scheltens, Nienke M.E.; Tijms, Betty M.; Koene, Teddy; Barkhof, Frederik; Teunissen, Charlotte E.; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Cohn‐Sheehy, Brendan I.; Rabinovici, Gil D.; Miller, Bruce L.; et al.
Abstract: Introduction: Patients with Alzheimer's disease (AD) show heterogeneity in profile of cognitive impairment. We aimed to identify cognitive subtypes in four large AD cohorts using a data‐driven clustering approach. Methods: We included probable AD dementia patients from the Amsterdam Dementia Cohort ( n = 496), Alzheimer's Disease Neuroimaging Initiative ( n = 376), German Dementia Competence Network ( n = 521), and University of California, San Francisco ( n = 589). Neuropsychological data were clustered using nonnegative matrix factorization. We explored clinical and neurobiological characteristics of identified clusters. Results: In each cohort, a two‐clusters solution best fitted the data (cophenetic correlation >0.9): one cluster was memory‐impaired and the other relatively memory spared. Pooled analyses showed that the memory‐spared clusters (29%–52% of patients) were younger, more often apolipoprotein E ( APOE ) ɛ4 negative, and had more severe posterior atrophy compared with the memory‐impaired clusters (all P < .05). Conclusions: We could identify two robust cognitive clusters in four independent large cohorts with distinct clinical characteristics. Highlights: Alzheimer's disease (AD) is a heterogeneous disorder. We identified two cognitive AD subtypes in four cohorts with a data‐driven approach. Nonamnestic AD is associated with distinct neurobiological characteristics.